Why do Europeans work part-time? A cross-country panel analysis. - Hielke Buddelmeyer; Gilles Mourre; Melanie Ward-Warmedinger (European Central Bank (ECB), 2008)
This empirical paper seeks to determine the relative contribution of the business cycle and structural factors to the development of part-time employment in the EU-15 countries over the 1980s and 1990s, exploiting a panel of EU countries. In the short-run, the business cycle is found to exert a short-term negative effect on part-time employment developments, which is consistent with firms utilising part-time work to adjust their labour force to changing economic conditions. Institutions and other structural factors such as changes in legislation affecting part-time employment are found to be key drivers of the rate of part-time employment, significant in the longer run. Overall, although the role of individual factors differs in the 1980s and 1990s, a contribution analysis considering the most significant factors shows that the main structural and institutional variables generally well explain the development in the part-time employment rate in the EU countries, which is not the case in the United States.
Keywords: J21; J22; J28; J68; 330; institutions; labour market policies; labour supply; Part-time employment; regulations; the business cycle; working time organisation; Teilzeitarbeit; Konjunktur; Arbeitsmarktpolitik; Arbeitsangebot; Institutionelle Infrastruktur; EU-Staaten